P50 Advance directives inclination of patients in singapore – a qualitative study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Wong, JCQ; Lau, CSL; Teo, LY; Khoo, CY; Ng, CT; Chan, LLH; Loh, JK; Sim, KLD
Abstract : This study aims to understand which of the advance directives (ADs) i.e. Advance Care Planning (ACP), Advance Medical Directive (AMD) and Lasting Power of Attorney (LPA) patients are more inclined to. The study was conducted from March to September 2018 in our institution. Patients aged 21 to 99 were asked to complete a survey to evaluate their awareness, perceptions and receptions on the ADs. Out of 150 patients, the awareness was 101 for LPA, 77 for AMD and 74 for ACP with 41.3%, 28.6% and 20.7% of them learnt about them through media respectively. 55 out of 101 patients considered doing LPA. 51 out of 77 patients considered doing AMD. 40 out of 74 patients considered doing ACP. 70% of those considering doing ADs are influenced by their family. 38.6% of them favoured LPA over ACP and AMD as financial arrangement is made. 30% of them prefer AMD to ACP as AMD is legal-binding. 36% of them prefer ACP to AMD as they get to discuss their healthcare preferences with their caregivers. 48% of them think it is too early to talk about end-of-life treatments. 51.3% of them do not know the process of doing ACP and AMD. There is no significant trend showing which ADs are patients more inclined to. Healthcare providers could initiate ACP conversations when patients are at their early disease trajectory. Also, more can be done to increase ADs awareness especially ACP through media to educate public on their importance and processes.